Dynamic Responses of Ammonia-Oxidizing Archaea and Bacteria Populations to Organic Material Amendments Affect Soil Nitrification and Nitrogen Use Efficiency - Zheng, Jie; Tao, Liang; Dini-Andreote, Francisco; Luan, Lu; Kong, Peijun; Xue, Jingrong; Zhu, Guofan; Xu, Qinsong; Jiang, Yuji (Frontiers in Microbiology, 2022)
Organic material amendments have been proposed as an effective strategy to promote soil health by enhancing soil fertility and promoting nitrogen (N) cycling and N use efficiency (NUE). Thus, it is important to investigate the extent to which the structure and function of ammonia-oxidizing archaea (AOA) and bacteria (AOB) differentially respond to the organic material amendments in field settings. Here, we conducted a 9-year field experiment to track the responses of AOA and AOB populations to the organic material amendments and measured the potential nitrification activity (PNA), plant productivity, and NUE in the plant rhizosphere interface. Our results revealed that the organic material amendments significantly enhanced the abundance and diversity of AOA and AOB populations. Further, significant differences were observed in the composition and co-occurrence network of AOA and AOB. A higher occurrence of potential competitive interactions between taxa and enumerated potential keystone taxa were observed in the AOA-AOB network. Moreover, we found that AOA was more important than AOB for PNA under the organic material amendments. Structural equation modeling suggested that the diversity of AOA and AOB populations induced by the potential competitive interactions with keystone taxa dynamically accelerated the rate of PNA, and positively affected plant productivity and NUE under the organic material amendments. Collectively, our study offers new insights into the ecology and functioning of ammonia oxidizers and highlights the positive effects of organic material amendments on nitrogen cycling dynamics.